Efeito imediato da estimulação elétrica neuromuscular seletiva do músculo VMO em pacientes com síndrome da dor femoropatelar - Augusto, Denise Dal'ava (2010)
Patellofemoral pain syndrome (PFPS) is described as anterior or retropatellar pain knee in the absence of other pathologies and is frequently associated with dysfunction of the vastus medialis oblique (VMO). However, several studies have demonstrated the inability to selectively activate this muscle through exercise. To evaluate the effect of Neuromuscular Electrical Stimulation (NMES) selective VMO in women with syndrome. We evaluated thirty-eight women: twenty in the control group (24.15 ± 2.60 years) and eighteen diagnosed with PFPS (25.56 ± 3.55 years). Both groups were evaluated before and after a protocol of electro stimulation. To measure for comparing groups before and after treatment, we assessed the extensor torque concentric and eccentric knee through an isokinetic dynamometer, the intensity (Root Mean Square - RMS) and the onset of activation (onset) of VMO compared to the vastus lateralis (VL) in two types of exercise: open and closed kinetic chain. . Statistical analysis was performed using SPSS 15.0, with a significance level of 5%. Results: Our data showed an increase in the intensity of activation (RMS) of the VMO muscle after NMES in both study groups. During concentric contraction the RMS of the VMO before the NMES was 105.69 ± 32.26 μV and after a single intervention was 122.10 ± 39.62 μV (p = 0.048) for the control group. In the group with PPS, we found a similar behavior, with RMS of the VMO before NMES of 96.25 ± 18.83 μV and 139.80 ± 65.88 μV after the intervention (p = 0.0001). However, there was no evidence in the RMS value of VL muscle. The onset was calculated by subtracting the onset of VL by the onset of VMO. For the group with PFPS, the onset before the intervention was -0.007 ± 0.14 ms, indicating a delay of the VMO relative to VL, and after NMES was 0.074 ± 0.09 ms (p = 0.016), showing an activation previous VMO to VL. The same occurred for the control group. We also observed that NMES increased knee extensor power during the concentric contraction in both groups. Before the intervention the mean power was 28.97 ± 9.01 W for the PPS group and after NMES was 34.38 ± 7.61 W (p = 0.0001). Conclusion: We observed an increase in electromyographic activity of the VMO and also an anticipatory effect of this muscle